2021
DOI: 10.1080/01480545.2021.1925691
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of tobacco-free “modern” oral nicotine pouches and their position on the toxicant and risk continuums

Abstract: 2021): Chemical characterization of tobacco-free "modern" oral nicotine pouches and their position on the toxicant and risk continuums, Drug and Chemical Toxicology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 34 publications
(33 reference statements)
4
81
0
8
Order By: Relevance
“…Nicotine pouches may appeal to young adults who use tobacco and might be interested in alternative nicotine products that lack pulmonary exposure, but also may appeal to young adult non-users of nicotine/tobacco products. Some evidence indicates that nicotine pouches have a toxicity level lower than combustible tobacco, approaching levels comparable to nicotine replacement therapy products [ 7 ]. The relative health effects of using nicotine pouches compared to e-cigarettes and other non-combustible tobacco products (e.g., heated tobacco products, snus) are unknown [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine pouches may appeal to young adults who use tobacco and might be interested in alternative nicotine products that lack pulmonary exposure, but also may appeal to young adult non-users of nicotine/tobacco products. Some evidence indicates that nicotine pouches have a toxicity level lower than combustible tobacco, approaching levels comparable to nicotine replacement therapy products [ 7 ]. The relative health effects of using nicotine pouches compared to e-cigarettes and other non-combustible tobacco products (e.g., heated tobacco products, snus) are unknown [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence indicates that nicotine pouches have a toxicity level lower than combustible tobacco, approaching levels comparable to nicotine replacement therapy products [ 7 ]. The relative health effects of using nicotine pouches compared to e-cigarettes and other non-combustible tobacco products (e.g., heated tobacco products, snus) are unknown [ 7 ]. However, nicotine pouches lack exposure to toxins present in some e-cigarettes, such as metals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike snus, however, NPs typically do not contain tobacco but pharmaceutical grade nicotine absorbed onto a cellulose matrix in a porous pouch [ 19 – 21 ]. The comparatively simple composition of NPs relative to snus is reflected in a recent toxicant analysis, which showed that NPs contain lower levels than snus of 10 harmful and potentially harmful tobacco constituents (HPHCs) and undetectable levels of a further 13 HPHCs [ 20 ]. In vitro studies also indicate that extracts from NPs are significantly less biologically active than extracts from Swedish snus or cigarette smoke [ 22 ], supporting a potential role of NPs in tobacco harm reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Studie uvádějí nižší hladiny toxinů v MOP ve srovnání se švédským snusem (23). Cytotoxicita nikotinového sáčku a švédského snusu je výrazně nižší než u cigarety, v případě nikotinového sáčku dokonce minimální (24).…”
Section: Rizikaunclassified